Confucian Iconoclasm : Textual Authority, Modern Confucianism, and the Politics of Antitradition in Republican China - Major, Phillippe, 1981- (Book collections on Project MUSE., 2023)
"Challenges deep-seated assumptions about the traditionalist nature of Confucianism by providing a new interpretation of the emergence of modern Confucianism in Republican China"--